2007
DOI: 10.1002/9780470985571.ch9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Insulin Resistance on Macrophage Death Pathways in Advanced Atherosclerosis

Abstract: Macrophage death in advanced atherosclerosis causes plaque necrosis, which promotes plaque rupture and acute atherothrombotic vascular events. Of interest, plaque necrosis and atherothrombotic disease are markedly increased in diabetes and metabolic syndrome. We discovered a novel 'multi-hit' macrophage apoptosis pathway that appears to be highly relevant to advanced atherosclerosis. The elements of the pathway include: (a) activation of the unfolded protein response (UPR) by cholesterol overloading of the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
0
11
1
2
Order By: Relevance
“…Hyperinsulinemia caused by insulin resistance directly stimulates the in vitro migration of neutrophils and monocytes in response to chemokines that are secreted by atherosclerotic plaques [27]. Hyperinsulinemia might promote atherosclerotic plaque necrosis by accelerating macrophage death [28]. In particular, hyperinsulinemia induces the production of matrix metalloproteinase-9 (MMP-9), which provokes plaque instability and rupture [29].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperinsulinemia caused by insulin resistance directly stimulates the in vitro migration of neutrophils and monocytes in response to chemokines that are secreted by atherosclerotic plaques [27]. Hyperinsulinemia might promote atherosclerotic plaque necrosis by accelerating macrophage death [28]. In particular, hyperinsulinemia induces the production of matrix metalloproteinase-9 (MMP-9), which provokes plaque instability and rupture [29].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, insulin directly increases neutrophil and monocyte in vitro migration in response to chemokines secreted in atherosclerotic plaques [129, 130]. Insulin could also favor atherosclerotic plaque necrosis by accelerating macrophage death [131]. Furthermore, insulin induces in vivo production of matrix metalloproteinase-9 (MMP-9), which is responsible for plaque instability and rupture [132134].…”
Section: Role Of Insulin Resistance In Atherosclerotic Plaque Instmentioning
confidence: 99%
“…A recent animal study indicated that elevated serum uric acid level exacerbates left ventricular diastolic dysfunction in mice fed a Western diet, which also leads to other pathophysiological processes, including myocardial hypertrophy, oxidative stress, interstitial fibrosis and macrophage proinflammatory polarization [14,15]. Monocytes/ macrophages have critical importance in the development of metabolic syndrome, including gout, obesity-related diseases, insulin resistance and atherosclerosis [12,[16][17][18][19]. However, the relationship between high uric acid (HUA) level and monocyte/macrophage activity remains unclear.…”
Section: Introductionmentioning
confidence: 99%